Cytokines and chemokines expression pattern in herpes simplex virus type-1 encephalitis. (15th October 2021) - Wang, Jiaojiao; Cheng, Yi; Ma, Yueting; Wu, Rihong; Xu, Yu; Yang, Shuling; Wang, Yongxia; Lin, Yingzi
Highlights: Cytokines/chemokines expression patterns in HSE animals were assessed using cytokine chip assay. 13 out of 62 factors in the array were found to be up-regulate in HSE. Most of the selected factors were involved in inflammation-related signal pathways. IL-6 might be a key mediator in the inflammatory responses to the disease. Abstract: To explore the differently expressed cytokines and chemokines to understand the pathways that lead to herpes simplex encephalitis (HSE). Mice in the experimental group were inoculated intracranially with HSV-1. A high-throughput cytokine chip assay was employed to assess the expression of cytokines/chemokines in the mice brain. GO, KEGG, and PPIs analyses were used to investigate the biological process (BP), pathways and interaction network of the differently expressed proteins (DEPs) in HSE. 13 DEPs and various proteins-related signal pathways were identified in HSE, including three new factors (IL-1α, MIP-1γ, and sTNF RI). The proteins were mainly implicated in leukocyte activation and chemotaxis. Additionally, the DEPs constituted a pivotal protein interaction network where IL-6 might be a mediator. 13 DEPs and a series of related signal pathways were associated with the pathophysiological mechanisms responsible for HSE. IL-6 might be a key mediator in the inflammatory responses to the disease.